A new algorithm for cluster analysis of genomic methylation - Vale, F. F. (2015)
Motivation: The genomic methylation analysis is useful to type bacteria that have a high number of expressed type II methyltransferases. Methyltransferases are usually committed to Restriction and Modification (R-M) systems, in which the restriction endonuclease imposes high pressure on the expression of the cognate methyltransferase that hinder R-M system loss. Conventional cluster methods do not reflect this tendency. An algorithm was developed for dendrogram construction reflecting the propensity for conservation of R-M Type II systems. Results: The new algorithm was applied to 52 Helicobacter pylori strains from different geographical regions and compared with conventional clustering methods. The algorithm works by first grouping strains that share a common minimum set of R-M systems and gradually adds strains according to the number of the R-M systems acquired. Dendrograms revealed a cluster of African strains, which suggest that R-M systems are present in H.pylori genome since its human host migrates from Africa.